Halifax's Nocturne versus(?) the spectacle of neo-liberal civics. (22nd June 2012) - Haiven, Max
Halifax's Nocturne: Art at Night has been met with almost universal enthusiasm from both the city's arts community as well as local political and business elites. This article argues that, while there is much laudable about events like Nocturne, and while many of the works and performances they feature are reflexive and critical, they risk participating in (and promoting) what I term 'neo-liberal civics'. Ironically, these public events take place and have resonance only within a cultural, social and political landscape already dramatically privatized, one where the meaning of 'creativity' has become a battleground.